Synchronic [videorecording (DVD)] - Benson, Justin; Benson, Justin; Benson, Justin; Moorhead, Aaron Scott, 1987-; Moorhead, Aaron Scott, 1987-; Dornan, Jamie, 1982-; Mackie, Anthony, 1978-; Aselton, Katie, 1978- (Well Go USA Entertainment, 2021)
Two New Orleans paramedics see their lives changed when they come across a series of horrific deaths which are linked to a desginer drug with bizarre side effects.